2011
DOI: 10.1111/j.1447-0756.2011.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant combined paclitaxel and carboplatin chemotherapy for glassy cell carcinoma of the uterine cervix: Report of three cases with clinicopathological analysis

Abstract: Glassy cell carcinoma of the uterine cervix (GCC) is a rare form of cervical carcinoma that is characterized by aggressiveness and poor prognosis. We reviewed a variety of clinicopathological features, treatment strategies, and outcomes in three women with GCC. The three patients were successfully treated by radical hysterectomy with pelvic/para-aortic lymphadenectomy. The patients had stage Ib1, stage IIa, and stage Ib2 tumors without lymph node metastases. A 44-year-old woman with stage Ib1 tumor did not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(25 reference statements)
1
4
0
2
Order By: Relevance
“…The findings of embryonic ducts spread in broad ligaments and under the fallopian tube serosa in our series could be related to studies describing occurrence of endometriomas as well as neoplasms of a Müllerian origin in these locations (Zacharia and O’Neill, 2006; Handa et al, 2007; Wei et al, 2011). Finally, the aberrant and consistent expression of alpha-1-fetoprotein revealed in the embryonic ducts in two fetuses is in accordance with other studies that reported de novo expression of this protein in ovarian malignancy arising from endometriosis (Horiuchi et al, 1998; Certin et al, 2007; Takahashi et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…The findings of embryonic ducts spread in broad ligaments and under the fallopian tube serosa in our series could be related to studies describing occurrence of endometriomas as well as neoplasms of a Müllerian origin in these locations (Zacharia and O’Neill, 2006; Handa et al, 2007; Wei et al, 2011). Finally, the aberrant and consistent expression of alpha-1-fetoprotein revealed in the embryonic ducts in two fetuses is in accordance with other studies that reported de novo expression of this protein in ovarian malignancy arising from endometriosis (Horiuchi et al, 1998; Certin et al, 2007; Takahashi et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…Its prognosis is poor due to its resistance to radiotherapy and chemotherapy, rapid progression, and recurrence tendency. [11][12][13] Although there have been reports of successful chemotherapy and radiotherapy, [13][14][15] surgery and postoperative CCRT were chosen in this case because of the difficulty of intracavitary radiotherapy; subsequently, a disease-free-interval of 9 months was achieved. Thus, treatment should be decided based on each case due to the lack of an exclusive one.…”
Section: Discussionmentioning
confidence: 99%
“…A principal característica anatomopatológica do câncer do tipo glassy cell é a quantidade moderada de citoplasma granular pálido com aspecto de vidro moído, núcleos localizados centralmente com nucléolo proeminente, membranas celulares distintas e proeminente infiltração de eosinófilos no estroma. 1 Receptores de estrogênio e progesterona foram encontrados em tumores do tipo glassy cell, sugerindo que este tumor pode ser responsivo a esses hormônios. 9 Kato e colaboradores 4 sugerem forte associação do tumor tipo glassy cell com o HPV 18, que poderia induzir a aparência "vítrea" do citoplasma possivelmente por induzir a diferenciação escamosa e glandular bifásica.…”
Section: Discussionunclassified
“…Foi descrito pela primeira vez em 1956 por Cherry e Gucksmann. 1 A idade média de incidência é de cerca de 10 anos menor do que a média de pacientes com carcinomas de células escamosas e de adenocarcinomas do colo do útero, 2 com pico de incidência entre a terceira e quarta décadas. 3 Seu comportamento clínico é caracterizado pela agressividade com rápido crescimento e progressão, metástases precoces e fraca resposta à radioterapia e cirurgia.…”
Section: Introductionunclassified